Effect of rapid thermal annealing on barrier height and 1/f noise of Ni/GaN Schottky barrier diodes - Kumar, Ashutosh; Latzel, Michael; Christiansen, Silke; Kumar, V.; Singh, R. (Applied Physics Letters, 2015)
Current-voltage (as a function of temperature), capacitance-voltage, and 1/f noise characteristics of Ni/GaN Schottky barrier diodes (SBDs) as function of rapid thermal annealing (RTA) are studied. It is found that RTA treatments of SBDs at 450 °C for 60 s resulted in a significant improvement of ideality factor and Schottky barrier height: the ideality factor decreased from 1.79 to 1.12 and the barrier height increased from 0.94 to 1.13 eV. The spectral power density of current fluctuations in the diode subjected to RTA at 450 °C is found to be two orders of magnitude lower as compared to the as-deposited diode. Improved diode characteristics and decreased 1/f noise in RTA treated (450 °C/60 s) diode are attributed to reduced level of barrier inhomogeneities at the metal-semiconductor interface and explained within the framework of the spatial inhomogeneity model.
EAM Import::2019-03-14